Medicinal plants documentation of Dayak Banuaq tribe in Intu Village, Nyuatan District, West Kutai, East Kalimantan - Lestari, Indah; Syafah, Lailiiyatus (University of Muhammadiyah Malang, 2019)
The Dayak Benuaq tribe is one of the tribes in Indonesia who live in East Kalimantan. They have various knowledge related to raw materials and medical treatment traditions for generations that have never been documented, especially in Intu Lingau Village, Nyuatan District, West Kutai, East Kalimantan. This study aims to documentation of medicinal plants and herbs of the local communities. The finding shows that there are 104 plants used, which is divided into 34 families. The most common plant parts used in the treatment were leaves, the most common processing method was boiling, and the most utilized method was by drinking.